Event-driven dynamic scheduling of discrete manufacturing - Chong, Chin Soon (2008)
This research seeks to address the new scheduling challenges through event-driven dynamic scheduling particularly for discrete manufacturing environment. The research investigates on how the performance of production scheduling can be maintained or even improved under production disruptions, using scheduling techniques.